Antibacterial activities of combination of ethanol extract of Delima fruit (Punica granatum L.) and Sereh stem (Cymbopogon citratus) on Staphylococcus aureus - Pebrina, Melia; Sari, Indah Komala; Arman, Eliza; Morika, Honesty Diana (International Journal Of Community Medicine And Public Health, 2019)
ABSTRACT Background: Pomegranates contain chemical saponins and flavonoids while lemongrass stems have flavonoid chemical compounds. Substances that can inhibit the linking of bacteria are saponins and flavonoids. The most common microorganism found in ulcus diabetikum (ulcer diabetes) is Staphylococcus aureus. The purpose of this study was to determine the antibacterial activity of a combination of pomegranate ethanol extract and ethanol extract of lemongrass stems against S. aureus bacteria. Methods: This study used an experimental design with a complete randomized design study divided into 5 groups: groups 1 (75:25), 2 (50:50), 3 (25:75), positive control (tetracycline) and negative control. Manufacture of pomegranate peel extract and lemongrass stems was done by maceration method for further rotary, after the extract was obtained tested for antibacterial activity by diffusion method using a cylinder. With the test used analysis of variance one way. Results: The results of this study showed that the combination of pomegranate ethanol extract and citronella stem ethanol extract showed activity against S. aureus with a ratio of 15 ul:5 ul, 15 ul:15 ul, 5 ul:15 ul with inhibitory diameter of respectively 13 mm, 11 mm, 8 mm. Whereas for positive control with chloramphenicol, the inhibition area is 9 mm. Conclusions: Statistically the combination of pomegranate ethanol extract and lemongrass stems has antibacterial power which uses p=0.005 and p<0.05. The combination of pomegranate ethanol extract and lemongrass stems has very strong antibacterial activity against S. aureus due to inhibition zones of 10-20 mm.